The Routledge Handbook of Architecture, Urban Space and Politics, Volume 1: Violence, Spectacle and Data,ed. Nikolina Bobic and Farzaneh Haghighi - Wanan, Samer (Interstices: Journal of Architecture and Related Arts, 2023)
***